Higher mortality of adults with asthma: A 15‐year follow‐up of a population‐based cohort. Issue 7 (15th March 2018) - Lemmetyinen, R. E.; Karjalainen, J. V.; But, A.; Renkonen, R. L. O.; Pekkanen, J. R.; Toppila‐Salmi, S. K.; Haukka, J. K.
Abstract: Background: Higher all‐cause mortality in asthmatics has been shown previously. Polysensitization is associated with higher morbidity among asthmatic children, and allergic rhinitis and/or allergic conjunctivitis (AR/AC) are associated with higher morbidity in adult asthmatics. Little is known about the effect of AR/AC and other factors on mortality among adult asthmatics. The aim was to study mortality and its risk factors in adults with and without asthma. Methods: We randomly selected 1648 asthmatics with age over 30 years from national registers and matched the asthma sample with one or two controls. Baseline information was obtained by a questionnaire in 1997, and the study population was linked with the death certificate information of Statistics Finland from 1997 to 2013. Overall and cause‐specific survival between the groups was compared in several adjusted models. Results: During a mean follow‐up period of 15.6 years, 221 deaths among 1052 asthma patients and 335 deaths among 1889 nonasthmatics were observed. Cardiovascular diseases were the main cause of death in both groups. Asthma was associated with increased all‐cause mortality (adjusted HR 1.25; 95% CI 1.05‐1.49, P = .011) as well as mortality from chronic obstructive pulmonary disease (HR 12.0, 4.18‐34.2, P < .001) and malignant neoplasms of respiratory organs (HR 2.33, 1.25‐4.42, P = .008). Among asthmatics, smoking was associated with increased all‐cause mortality, and self‐reported AR/AC was associated with decreased mortality. Among nonasthmatics, smoking, and obesity were associated with increased all‐cause mortality, whereas female gender showed an association with a decreased risk. Conclusions: Increased mortality among adult asthmatics was largely explained by the development of COPD, malignant respiratory tract neoplasms, and cardiovascular diseases. Smoking cessation is important for reduction in total mortality in both asthmatic and nonasthmatic adults. AR/AC was associated with decreased mortality only in asthmatics. Thus, studies in other populations of larger size are needed to explore further the nature of this association.